Identification of factors required for m6A mRNA methylation in Arabidopsis reveals a role for the conserved E3 ubiquitin ligase HAKAI. Issue 1 (15th May 2017) - Růžička, Kamil; Zhang, Mi; Campilho, Ana; Bodi, Zsuzsanna; Kashif, Muhammad; Saleh, Mária; Eeckhout, Dominique; El‐Showk, Sedeer; Li, Hongying; Zhong, Silin; De Jaeger, Geert; Mongan, Nigel P.; et al.
Summary: N 6‐adenosine methylation (m 6 A) of mRNA is an essential process in most eukaryotes, but its role and the status of factors accompanying this modification are still poorly understood. Using combined methods of genetics, proteomics and RNA biochemistry, we identified a core set of mRNA m 6 A writer proteins in Arabidopsis thaliana . The components required for m 6 A in Arabidopsis included MTA, MTB, FIP37, VIRILIZER and the E3 ubiquitin ligase HAKAI. Downregulation of these proteins led to reduced relative m 6 A levels and shared pleiotropic phenotypes, which included aberrant vascular formation in the root, indicating that correct m 6 A methylation plays a role in developmental decisions during pattern formation. The conservation of these proteins amongst eukaryotes and the demonstration of a role in writing m 6 A for the E3 ubiquitin ligase HAKAI is likely to be of considerable relevance beyond the plant sciences.